STUDI PERBANDINGAN RELIGIUSITAS SISWA KELAS XI YANG AKTIF DAN TIDAK AKTIF DALAM KEGIATAN EKSTRAKURIKULER (ROHIS) DI SMA NEGERI 2 RAMBAH HILIR KABUPATEN ROKAN HULU - Purwati, Ida Purwati Ida; ', Hambali; ', Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research conducted because of this study religious behavior religiosity student or students at SMAN 2 Rambah Hilir virtually indistinguishable between students who are active and nonactive Rohis. So writer take the title "Comparative Study of Religiosity of Students Active and Non Active in Extracurricular Activities (Rohis) at SMAN 2 Rambah Hilir Rokan Hulu Regency". Formulation of the problem in this research is how religiosity comparison class XI students active and not active in extracurricular activities (Rohis) at SMAN 2 Rambah Hilir Rokan Hulu Regency. The purpose of this study was to determine how the comparison religiosity Class of XI students active and not active in extracurricular activities (Rohis) at SMAN 2 Rambah Hilir Rokan Hulu Regency. Extracurricular activities Rohis have a very big role in the improvement of students' religious attitude that is as a motivator, creator, innovator, integrator, and Sublimator-. This is evidenced by the awareness of students to worship and morality against Allah, parents, teachers, peers, and the environment (Mushbihah Rodliyatun, 2013). The sampling technique used in this study is simple random sampling. The population in this study is 123 students and the sample amounted to 62 students, which is active Rohis 31 students and 31 students were inactive Rohis. Namely data collection techniques through observation, interviews, documentation, and questionnaires. The main data derived from the questionnaire, consisting of demographic questions and religiosity students 4 students 29 questions. Data were analyzed with descriptive quantitative. Data were analyzed by percentage. From the calculation of the percentage of respondents, obtained religiosity students active and inactive Rohis Rohis have differences. Based on statistical tests to determine whether there are differences in religiosity students active and inactive Rohis by using t-test formula obtained t = 3.37, then ttable with level of confidence 95% (a) = 0,05 was obtained ttabel = 2.00 , So, thitung Ëƒ ttable or 3.27 Ëƒ 2.00. Thus, it can be concluded that Ha is accepted that there are significant differences in religiosity between class XI students active and not active in extracurricular activities (Rohis) at SMAN 2 Rambah Hilir Rokan Hulu Regency. Key words: Religiosity, Extracurricular (Rohis), Students